Penerapan Model Problem Based Learning untuk Meningkatkan Keterampilan Berpikir Kritis Siswa Pada Materi Koloid di Kelas XI SMAS Hidayatullah Kendari - Abdul Kahar; Fahyuddin; Muhammad Alim Marhadi (Jurnal Riset Pendidikan Kimia (JRPK), 2025)
The research "Application of Problem Based Learning Model to Improve Students' Critical Thinking Skills on Colloid Material in Class XI SMAS Hidayatullah Kendari" improves students' critical thinking skills by applying problem based learning model to improve students' critical thinking skills on colloid material in class XI SMAS Hidayatullah Kendari on the main material of colloid, knowing the effectiveness of applying Problem Based Learning model on colloid material, knowing how students respond to Problem Based Learning model. The research method used is pre-experimental with One-Group Pretest-posttest design. Data collection techniques use pretest-posttest, observation sheets, and questionnaire sheets. The results of the study show that the learning outcomes of class XI SMAS Hidayatullah Kendari students who are taught using the Problem Based Learning model obtained an average value of 74.7. The contribution or influence of Problem Based Learning on improving students' critical thinking skills on Colloid material in class XI SMAS Hidayatullah Kendari can be seen from the R Square value in the Summary model table, appendix 13, which is 0.840 or 84%. Thus, the magnitude of the influence of the Problem Based Learning model on improving students' critical thinking skills is 84%. Teacher activity in the first meeting was 72.5%, the second meeting increased to 77.5%. The student response questionnaire using Problem Based Learning showed that the student motivation aspect had an average of 89.04, the student responsibility aspect had an average of 79.14, the student material mastery aspect had an average of 84.36, and the student presentation aspect of discussion results had an average of 43.69.